Thermal annealing tailors crystallinity and magnetism in silica coated Ni-Zn ferrite (SiO2@NiZnFe2O4) nanoparticles - Widakdo, Januar (Greensusmater, 2025)
Ni0.5Zn0.5Fe2O4 nanoparticles were synthesized using a co-precipitation method followed by annealing at different temperatures to investigate their structural, morphological, and magnetic properties. X-ray diffraction (XRD) confirmed the formation of a single-phase spinel structure, with increased crystallinity and grain growth observed at higher annealing temperatures. Transmission electron microscopy (TEM) and selected area electron diffraction (SAED) further revealed a transition from small, aggregated nanoparticles to well-defined crystalline grains. Magnetic hysteresis measurements demonstrated a significant enhancement in saturation magnetization (Ms) and coercivity (Hc) with increasing temperature, reaching up to 55.15 emu/g and 253.23 Oe, respectively, at 800 °C. These improvements are attributed to reduced surface spin disorder and increased magnetic domain alignment due to grain growth. The results underscore the importance of annealing temperature in tailoring the magnetic behavior and structural properties of Ni–Zn ferrite nanoparticles for potential applications in magnetic and electronic devices.